2020
DOI: 10.3390/e22111218
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Comprehensive Evaluation Method for Estimating the Bank Profile Shape and Dimensions of Stable Channels Using the Maximum Entropy Principle

Abstract: This paper presents an extensive and practical study of the estimation of stable channel bank shape and dimensions using the maximum entropy principle. The transverse slope (St) distribution of threshold channel bank cross-sections satisfies the properties of the probability space. The entropy of St is subject to two constraint conditions, and the principle of maximum entropy must be applied to find the least biased probability distribution. Accordingly, the Lagrange multiplier (λ) as a critical parameter in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The specific evaluation steps are as follows (Zhao et al, 2018;Bonakdari et al, 2020): First, calculate the proportion of the measurement item i in the index j.…”
Section: Methodsmentioning
confidence: 99%
“…The specific evaluation steps are as follows (Zhao et al, 2018;Bonakdari et al, 2020): First, calculate the proportion of the measurement item i in the index j.…”
Section: Methodsmentioning
confidence: 99%
“…For rivers, the entrainment threshold is one such mechanical constraint; yet, models that invoke extremal hypotheses do not formally apply this constraint. Researchers have posited that rivers adjust their channel geometry to maximize flow resistance 67,68 , maximize entropy 69 , or maximize sediment transport 148,149 . There is, however, no physical basis for predicting this 'optimal' river configuration; one can only assert that the observed state of a river is optimal.…”
Section: Alternatives To the 1 + ε Modelmentioning
confidence: 99%
“…Yet, others have observed that such discrepancies may arise from mischaracterization of the threshold condition and the near-threshold model itself 6,52,66 . Alternative models for hydraulic geometry have proliferated, based on: optimization of sediment transport [67][68][69][70][71] ; feedback between flow resistance and channel form 72,73 ; and geotechnical stability of river banks 74 .…”
Section: Introductionmentioning
confidence: 99%
“…Whenever no velocity data are available, expeditive entropy-based models might be used for the assessment of the vertical velocity profile in order to derive local velocity gradients and, thus, bed shear stress [24,25]. The hydraulic methods are suggested for use in catchment areas where hydrometric observations are not available, or for controlled cross-sections [26][27][28][29][30]. Furthermore, in the flow-habitat models, ecological flow is calculated from interactions between the water discharge and the riverbed morphology, rather than establishing the suitable habitat conditions corresponding to the local morphological conditions.…”
Section: Introductionmentioning
confidence: 99%